The Framework of Multicultural Education Value in Indonesia Schools to Face Challenge of 21-Century Learning Using Literary Study - Arini Noor Izzati; Liliana Muliastuti; Zainal Rafli (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study uses literary analysis to provide a model for how multicultural education might help Indonesian schools meet the challenges of the twenty-first century. This study fills a knowledge vacuum by employing works of fiction to investigate the importance of intercultural education. The novel Negeri 5 Menara also depicts a multicultural lifestyle and educational system. In this investigation, we employ a qualitative strategy based on content analysis. The study's data comes from a search for examples of intercultural education's core values in literature. This study used a selected data gathering method that Huberman and Miles refer to as "data reduction," consisting of five steps: selecting, focusing, simplifying, summarising, and modifying the raw data. Credibility, transferability, dependability, and confirmability are all aspects of data validity that should be examined. According to the study's findings, 1) multicultural education is beneficial because it teaches students to respect and tolerate diverse points of view during the decision-making process; 2) students can benefit from multicultural education both inside and outside the classroom; and 3) the value of multicultural education can be broken down into three main value components: democracy, pluralism, and humanism. The similarities in the concept of pluralism values, cultural empowerment as a basis for freedom of cross-cultural understanding, and the combination of content and knowledge construction in the education system are all examples of the framework of the multicultural education model that emerges from the analysis results. The findings of this study have relevance for the advancement of science, particularly for the study of literature across disciplines.